Pengaruh Fluktuasi Harga Emas, Tingkat Inflasi, dan Non Performing Financing Terhadap Penyaluran Pembiayaan Produk Gadai Emas - Shafira Aristianti; Bambang Waluyo; Ady Arman (LPMP Imperium, 2021)
This study aims to analyze the effect of gold price fluctuation, inflation rate, and Non-Performing Financing (NPF) on the distribution of gold pawn products at Mandiri Sharia Bank period 2011-2018. The analysis method used in this study is multiple regression analysis, with a total sample of 32 data. This study shows that gold price fluctuation, inflation rate, and NPF simultaneously have a positive and significant effect on the distribution of gold pawning products at Bank Syariah Mandiri. Partially shows that the inflation rate has a positive and significant impact, NPF has a negative and significant effect on the distribution of gold pawn products at Mandiri Sharia Bank. In contrast, gold price fluctuation does not positively and significantly affect the distribution of gold pawn products at Bank Syariah Mandiri. This study is expected to be helpful as an additional reference for Mandiri Sharia Bank in making policies to increase the distribution of gold pawn products at Bank Syariah Mandiri.